On-line separation of strontium from a matrix and determination of the 87Sr/86Sr ratio by Ion Chromatography/Multicollector-ICPMS. Issue 7 (23rd May 2016) - Karasinski, Jakub; Bulska, Ewa; Wojciechowski, Marcin; Krata, Agnieszka Anna; Halicz, Ludwik
Abstract : In this work a high throughput, robust and sensitive method for the precise isotopic analysis of 87 Sr/ 86 Sr by coupling Ion Chromatography (IC) and Multicollector Inductively Coupled Plasma Mass Spectrometry (MC-ICPMS) is presented. Abstract : In this work a high throughput, robust and sensitive method for the precise isotopic analysis of 87 Sr/ 86 Sr by coupling Ion Chromatography (IC) and Multicollector Inductively Coupled Plasma Mass Spectrometry (MC-ICPMS) is presented. The effective separation of Sr from a sample matrix by IC enables on-line isotopic determination of the 87 Sr/ 86 Sr ratio in transient signals by MC-ICPMS, without laborious off-line and time consuming sample preparation step and the need for clean room facilities. Mass discrimination and instrument drift were corrected by using the natural constant 86 Sr/ 88 Sr ratio as an internal standard. A precision (2 σ ) of the 87 Sr/ 86 Sr ratio of 0.003% was achieved in natural fresh water and high salinity samples, e.g. Dead Sea water, as well as carbonate and silicate rocks. Robustness, relatively high precision and accuracy, as well as minimum possibility of sample contamination of the developed analytical method have been demonstrated in complex natural samples of water and rocks as well. This method for the first time reports a possibility of isotopic analysis of cations by on-line IC separation with precision close to that obtained by an off-line technique.